(untitled) (Sebha University Conference Proceedings, 2025)
Liquid radioactive waste is one of the problems facing many countries at the present time, which requires treatment due to its impact on humans and the environment. In this study, the focus was on using some dry plant leaves from the farms surrounding the nuclear research center and conducting some experiments on them by using them as an ion exchanger to separate the thorium element in water containing radioactive waste that was prepared in the laboratory. Through the experiments and results obtained from this study, it can be concluded that the best results were obtained by using dried mulberry leaves as an ion exchanger in an acidic medium between (1.5-4) of nitric acid, and the lowest results were obtained at a pH of (0.5), followed by castor leaves in an acidic medium (5-4), and the lowest results were obtained by using fig leaves. When comparing the results obtained and measured by the spectrophotometer and the alpha spectrometer, it can be concluded that the loss rate in both cases was higher for the samples measured using the alpha spectrometer, as they passed through several steps, including evaporation, separation, and electro-deposition, and the results were higher than those measured by the spectrophotometer. (This study was conducted in the laboratories of the Tajoura Nuclear Research Center in May 2021)